Analisis Kebutuhan Media Pembelajaran Mengevaluasi Informasi dalam Teks Negosiasi di SMA - Al Abil Hidayatullah; Dina Ramadhanti; Trisna Helda (Universitas Muhammadiyah Jember, 2025)
This research aims to describe the needs analysis of learning media to evaluate information in negotiation text at SMAN 15 Padang. The needs analysis includes learning needs analysis, learning objectives, learners' characteristics, and learning environment to evaluate information in negotiation text. By using qualitative approach and description method, the data obtained through observation, interview, and questionnaire were analyzed in depth. The results showed that students at SMAN 15 Padang, in terms of learning needs, need access to technology in the form of negotiation simulation videos with interactive animations that visualize the negotiation process; in terms of learning objectives, students need media that help them unravel the structure of negotiation texts, assess arguments, and practice negotiations; in terms of learner characteristics, students generally like visual media and gamification so they need media that can facilitate various learning styles of students; and in terms of learning environment, students need access to interactive media, google docs for joint evaluation, and comfortable classrooms. Thus, students need learning media that is contextual/relevant to their daily lives, participatory/demanding students to be creative, adaptive to their diverse learning styles, and feedback such as quizzes to measure their skills.